Removal of TDS, Fe, Oil and Greases of Laboratory Wastewater using Ceramic Membrane Technology - Destri Yunita; Muhammad Faizal; Suheryanto Suheryanto (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Biochemistry Laboratory and Medicinal Chemistry as supporting facilities for practicum and research results in wastewater, which contains organic matter and suspended solids, such as TDS, Fe, Oil and Greases. If wastewater discarded directly to the drainage without passing sewage treatment system, then it potentially pollutes the environment and endangers the lives of living creatures. The purpose of this research is to evaluate the effectivity of the filtration system using ceramic membrane filtration technology to reduce the amount of TDS, Fe, Oil and Greases on laboratory’s wastewater. The filtration process is using ceramic membrane made of clay, activated carbon from lignite, and Fe powder. Pretreatment is done with the neutralization using NaOH 5N and coagulation using aluminum sulfate 400 mg/L. Variable in this research is the operating time of 5 and 20 minutes with operating pressure 1 kg/cm2. The result of this research shows that after 20 minutes operating, the reduction percentage of TDS, Fe, Oil and Greases after the process using ceramic membrane filtration technology were 0.97; 96.01; and 91.03 %, respectively. As the conclusion, the ceramic membrane is able to reduce the parameter of wastewater optimally. Keywords: ceramic membrane, coagulation, laboratory wastewater, lignite coal